Addressing challenges and barriers to rural Veteran participation in clinical research within the Veterans Affairs healthcare system - Marcus R. Johnson; Aliya Asghar; Danielle J. Beck; Tassos Kyriakides; Matthew P. Vincenti; Grant D. Huang (Contemporary Clinical Trials Communications)
The execution of clinical research in medical facilities that serve rural populations and/or that have lower care complexity levels has been proven to be challenging, as compared to larger healthcare institutions with higher complexity levels. Issues such as isolation, lack of organizational support and resources, difficulty with enrollment of study participants in rural settings, and challenges with identifying and retaining experienced clinical research staff serve as barriers to developing and establishing the necessary infrastructure to conduct clinical research at rural and/or smaller medical facilities. The United States (U.S.) Department of Veterans Affairs’ (VA) has the largest integrated health care system in the country and provides care to over 9 million Veterans. These considerations, combined with feedback collected from a subset of these types of (VA) Medical Centers (VAMCs) on this topic, demonstrate the need for a comprehensive enterprise-level strategy to address these challenges within the VA healthcare system. The VA Cooperative Studies Program (CSP) is a clinical research infrastructure that has vast expertise in the conduct of multi-site clinical research within the VA and is well poised to lead this effort.This manuscript describes the CSP “Advancing Capacity for Clinical Research through Engagement with Strategic Sites (ACCESS)” initiative. It focuses specifically on the successes, challenges, and lessons learned from the CSP ACCESS Workgroup (AW) during the development and implementation of a comprehensive pilot plan for engaging rural/lower complexity VAMCs (strategic sites) to participate in CSP clinical research.